Anterior Tooth Discrepancy in Different Bangladeshi Malocclusion Group at BSMMU - Hasan, Md Nazmul; Hassan, Gazi Shamim; Rafique, Tanzila; Alam, Mohammad Khursheed (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Anterior tooth discrepancy, an important clinical orthodontic tool to manage malocclusions, may vary on different race, ethnicity and gender. Therefore this study on anterior tooth discrepancy of Bangladeshi malocclusion groups were formulated to calculate and set up a standard norm, and to evaluate the gender discrepancy. A cross sectional type study was done among 207 pretreated dental casts (60 male, 147 female) of malocclusion patient at the Department of Orthodontics, Faculty of Dentistry, BSMMU, Bangladesh. Bolton anterior ratio were measured and compared statistically (in the Angles group of malocclusion). No significant anterior discrepancy was observed between Bangladeshi male and female groups. A similar value for anterior discrepancy was observed in neighboring countries. J Bangladesh Coll Phys Surg 2015; 33(4): 191-194